Greening the Economy in Afghanistan – Role of the Critical Mineral Mining Industry - Tantashev, Rinat; Eshchanov, Bahtiyor (Journal of Finance and Financial Law, 2024)
This article explores the current state and future prospects of developing a green economy in Afghanistan, focusing on renewable energy and fossil resources. It also examines regional cooperation and Afghanistan’s politico-economic relations with its neighbors, especially Uzbekistan. Afghanistan has a significant potential for a green economy due to its reserves of lithium and rare earth metals, essential for modern green technologies. The country is rich in renewable energy resources, which could address environmental challenges, reduce fossil fuel dependence, and create new economic opportunities. This study looks into renewable energy infrastructure, sustainable agriculture, and related challenges and opportunities. The paper starts by providing a literature review which analyzes the data on Afghanistan’s geology, economy, and environmental issues. It conducts stakeholder analysis by collecting data on perceptions and expectations from local communities, environmental organizations, and industry experts. The analysis is conducted through reviewing the current mining sector policies and comparing them with successful international models to propose policy reforms. Key areas for development include expanding renewable energy infrastructure, such as solar and wind power projects, and promoting sustainable agriculture practices. International organizations and donors are supporting these initiatives. In conclusion, Afghanistan’s transition to a green economy is viable and beneficial, requiring sustained efforts from the government, international partners, and the private sector. Strategic investments and cooperation can unlock the full potential of Afghanistan’s green economy, contributing to sustainable development and environmental protection.